Cultivating Spiritual Intelligence as an Effort to Build Student Leadership Spirituality in Theological College - Yusak Tanasyah; Bobby Kurnia Putrawan (Badan Musyawarah Perguruan Tinggi Keagamaan Kristen Indonesia, 2022)
The purpose of this study is to seek the growth of spiritual intelligence in Christian universities which is shown by the spirituality of student leadership. Students are future leaders in organizations, both in church, community, and other public fields. During the four years, students spend pursuing undergraduate programs at Christian higher education institutions, students learn and experience many types of leadership either through their capacity as leaders or as team members. Qualitative research observing the growth of students in Christian universities in the fields of theology and Christian religious education found that spiritual intelligence through student group activities both in coursework and extracurricular activities students can develop spiritual intelligence in growing their leadership spirituality. Therefore, the role of educators in pursuing student leadership spirituality in guiding and fostering student leadership is very necessary.